Thermodynamic interactions and characterisation of poly[(glycidyl methacrylate-co-methyl, ethyl, butyl) methacrylate] by inverse gas chromatography - Kaya, I; Ilter, Z; Senol, D (Elsevier Sci Ltd, 2002)
Poly(glycidyl methacrylate-co-methyl methacrylate) poly(GMA-co-MMA), poly(glycidyl methacrylate-co-ethyl methacrylate) poly(GMA-co-EMA) and poly(glycidyl methacrylate-co-butyl methacrylate) poly(GMA-co-BMA) were synthesized in 1,4-dioxane solution using 2,2'-azobisisobutyronitrile (AIBN) as initiator at 60 degreesC. The copolymer compositions were determined by H-1 NMR analysis. The FTIR and 13 C NMR spectra of the copolymers have been discussed. According to TG, carbonaceous residue values of poly(GMA-co-MMA), poly(GMA-co-EMA) and poly(GMA-co-BMA) were found to be 3.00, 4.00 and 4.20%, respectively, at 500 degreesC. Some thermodynamic quantities such as the sorption enthalpy, DeltaH(1)(s), the sorption entropy, TDeltaS(1)(s), the sorption free energy, DeltaG(1)(s), the partial molar free energy, DeltaG(1)(infinity), the partial molar heat of mixing, DeltaH(1)(infinity), at infinite dilution were obtained for the interactions of poly[(glycidyl methacrylate-co-methyl, ethyl, butyl) methacrylate] with n-alkanes, aromatics, CCl4, 1-chloro-propane, 1-chloro-butane and 1,4-dioxane by inverse gas chromatography method in the temperature range of 363-453 K. The specific retention volumes, V-0, the weight fraction activity coefficients of solute probes at infinite dilution, Omega(1)(infinity), Flory-Huggins thermodynamic interaction parameters, chi(12)(infinity) between polymers and solvents were determined. Also, the solubility parameters, 82, of the poly(GMA-co-MMA), poly(GMA-co-EMA) and poly(GMA-co-BMA) was found to be 30.85, 25.83, 25.00 (J cm(-3))(0.5) and 31.94, 26.59, 25.71 (J cm(-3))(0.5) from slope and intercept of [(delta(1)(2) IRT) - chi(12)(infinity)/V-1] = (2delta(2)/RT)delta(1) - delta(2)(2)/IRT equation, at 433, 423 and 393 K, respectively. The glass transition temperature, T-g, of the poly(GMA-co-MMA), poly(GMA-co-EMA) and poly(GMAco-BMA) was found to be 373, 355 and 334 K, respectively, by DSC and inverse gas chromatography. (C) 2002 Published by Elsevier Science Ltd.
Keywords: poly[(glycidyl methacrylate-co-methyl ethyl butyl) methacrylate]; inverse gas chromatography; polymer-solvent interactions